(untitled) (Faculty of Education Scientific Journal, 2024)
The aim of this research is to find out the reasons for the low academic achievement of primary school students from the point of view of their teachers in Misurata schools. The two researchers used the descriptive approach and the study sample was chosen randomly. The current research sample consisted of (300) male and female teachers in Misurata schools, while the basic research sample consisted of Of 300 teachers, including males and females, in the city of Misurata for the academic year 2022/2023 AD. The researchers also used a measure of low academic achievement as a tool for collecting data, and the results of the current research directed to: pay attention to developing the teaching performance of teachers, and to pay attention to solving problems in teaching practices Creating integrated training programs in teaching strategies in assistance with experts from the Curriculum and Teaching Methods Department in the Ministry according to the various specializations Continuous communication between the family and the school, cooperation in following up on the student, and activating and focusing the role of the psychological and social specialist in solving students’ problems.